1998
DOI: 10.1007/pl00009706
|View full text |Cite
|
Sign up to set email alerts
|

The partitioning of carbohydrates and the biomass of leaves in Populus tremula L . canopy

Abstract: AbstractmThis study was aimed at making a quantitative evaluation of the biomass, carbohydrates and mineral nutrients partitioning in the canopy of aspen (Populus tremula L.) growing in a forest stand. Tree canopy biomass was divided into ten equal horizontal layers and the material for the study was sampled from all canopy layers. The results indicated that the specific leaf mass and the dry matter content increased but the area of leaves decreased toward the top of the canopy. The content of the nonstructura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In Finland the mean foliar N concentration of 5-year-old hybrid aspens has been measured as 2.61%, the mean single leaf area as 18.44 cm 2 and the mean LWA as 72.3 g m À2 (Yu, 2001). In Estonia the average foliar NPK concentrations in a 35-year-old P. tremula stand have been measured as follows: N 1.9%, P 0.15% and K 1.5% (Mandre et al, 1998). According to the current study the average foliar N and P concentrations in 5-year-old hybrid aspen stands were slightly greater and the concentration of K was two times smaller.…”
Section: Discussionmentioning
confidence: 99%
“…In Finland the mean foliar N concentration of 5-year-old hybrid aspens has been measured as 2.61%, the mean single leaf area as 18.44 cm 2 and the mean LWA as 72.3 g m À2 (Yu, 2001). In Estonia the average foliar NPK concentrations in a 35-year-old P. tremula stand have been measured as follows: N 1.9%, P 0.15% and K 1.5% (Mandre et al, 1998). According to the current study the average foliar N and P concentrations in 5-year-old hybrid aspen stands were slightly greater and the concentration of K was two times smaller.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study we collected leaf samples from the upper canopy, whereas Jug et al (1999) collected from main shoots, supposedly from all canopy layers. For P. tremula it has been observed that foliar N does not significantly vary between different canopy layers, but P and K decrease towards the top of the canopy and could be 13% and 30% respectively higher in the lowermost canopy fraction (Mandre et al 1998). There could be differences between pot (ex-situ) and field (in-situ) experiments.…”
Section: Nutritional Status Of 7-yr-old Hybrid Aspensmentioning
confidence: 96%
“…It was shown earlier that photosynthetic properties vary vertically in crowns for both broadleaved and coniferous trees (Kozlowski et al 1991;Mandre et al 1998;Grassi and Bagnaresi 2001). This allows us to assume also existence of variation in nutrient partitioning in different parts of the crown.…”
Section: Partitioning Of Mineral Elements Between Crown Layersmentioning
confidence: 96%
“…As tree crowns are characterised by gradients of light, temperature and water supply between the crown top and bottom (Pearcy and Sims 1994;Niinemets et al 2007), foliar photosynthetic capacity (Grassi and Bagnaresi 2001;Han et al 2003;Marcelis and Heuvelink 2007), carbohydrate concentration (Mandre et al 1998) and anatomical characteristics (Richardson et al 2001), our emphasis was on detailed comparison of the allocation of mineral elements dominating in cement dust in Scots pine crown and their concentration in soil at different distances from the emission source. Nutrient partitioning in trees can be influenced by a variety of internal and external factors, and the question whether a particular organ is adequately supplied with assimilates and can therefore fully realise its growth potential may not have a simple answer.…”
Section: Introductionmentioning
confidence: 99%